LIFELONG EDUCATION IN MALAYSIA: EREDICATING ILLITERACY OR SOCIAL SAFETY NETS? - Awang, Saadon (European Scientific Journal, ESJ, 2015)
A basic principle to any education system is to allow people access to education, at least to make them able to read and write to fulfill various needs of daily lives. Normally, a government introduces an education system as a mechanism to achieve one development standard, which is measured by literacy rates amongst the population. Meanwhile, there are also some needs of the people to get education as far as they want, anytime and anywhere, in order to help nation achieves its rapid development. This paper attempts to explain the aim of lifelong education provided in Malaysia, whether it is just as to ensure every citizen is able to read and write, in order to achieve the standard of nation’s development, or aimed at preparing future work force who can survive in the wave of nation’s development in the future. Results of analysis revealed some findings, which is mostly in supportive of the idea about the needs for education systems, including lifelong education, is merely as Social Safety Nets to each individual to survive in the ever competitive environment in the future.